Analysis of water cresting in horizontal wells (2009)
Horizontal well application has sometimes been employed as a way of minimizing excessive water production arising from coning commonly encountered during oil production in vertical wells. Lots of efforts on water coning in vertical wells have been published. Available predictive models in horizontal wells vary from rather simplistic to complex models. This study investigated the development of practical models that combine ease of use with accuracy. Conformal mapping was used to combine steady state flow, volumetric voidage and pressure drop due to gravity effects in horizontal wells to obtain models that predict critical rates and breakthrough times. The results were compared with some existing correlations under varied reservoir fluid and rock properties. The models were also applied to vertical wells. It was also observed that critical rates and breakthrough times in horizontal wells are affected directly by effective permeability, well length, oil column height, density contrast between wafer and oil, !he height of the water crest. There is however, an inverse relationship with oil viscosity and production rate. It is concluded that simple and accurate correlation that can be applied to coning problems in both horizontal and vertical wells have been developed. They provide a means of comparing the performance of horizontal and vertical wells.